The Influence of Perceived Quality, Brand Image, and Customer Value on Satisfaction Through Purchase Decisions in the Coffee Market: The Moderating Role of Product Availability - Hermawan, Iwan; Rustono, Rustono; Taviyastuti, Taviyastuti; Rini, Nur; Luthfia, Irin Mirrah (RSF Conference Series: Business, Management and Social Sciences, 2025)
The coffee industry in Indonesia is growing rapidly, necessitating a deep understanding of the factors that influence purchasing decisions and customer satisfaction. This study tests a conceptual model linking Perceived Quality, Brand Image, and Customer Value to Customer Satisfaction, using Purchase Decision as a mediator and Product Availability as a moderator. The study is grounded in Expectation Confirmation Theory, which states that satisfaction arises from the alignment between initial expectations and actual experiences. Using quantitative methods, a survey was conducted among 618 coffee consumers in Indonesia. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The results showed that Perceived Quality, Brand Image, and Customer Value significantly influence Purchase Decision. Furthermore, Purchase Decision indirectly influences Customer Satisfaction through mediation, validating the theory that experiences consistent with expectations create satisfaction. An interesting finding emerged from the Product Availability variable. This variable was not significant in moderating the relationship between Purchase Decision and Customer Satisfaction. This is explained by the competitive market, where consumers have many options. However, Product Availability was significant in strengthening the relationship between Perceived Quality and Customer Satisfaction, indicating that consistent product availability directly shapes initial expectations and quality perceptions. Theoretically, this study contributes by applying a moderated mediation approach within the Expectation Confirmation Theory framework. Practically, these results have strategic implications for coffee shop managers to focus on managing quality perceptions, strengthening the brand, creating added value, and optimizing distribution to enhance consumer loyalty.